2020
DOI: 10.1186/s12935-020-01581-5
|View full text |Cite
|
Sign up to set email alerts
|

The emerging roles of non-coding competing endogenous RNA in hepatocellular carcinoma

Abstract: Accumulating evidence has emerged revealing that noncoding RNAs (ncRNAs) play essential roles in the occurrence and development of hepatocellular carcinoma (HCC). However, the complicated regulatory interactions among various ncRNAs in the development of HCC are not entirely understood. The newly discovered mechanism of competing endogenous RNAs (ceRNAs) uncovered regulatory interactions among different varieties of RNAs. In recent years, a growing number of studies have suggested that ncRNAs, including long n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 163 publications
1
25
0
Order By: Relevance
“…Several recently conducted researches have pointed out that lncRNA expression disorders actively participate in the development of tumors (23)(24)(25)(26)(27). In OSCC, more and more -196 (32).…”
Section: Discussionmentioning
confidence: 99%
“…Several recently conducted researches have pointed out that lncRNA expression disorders actively participate in the development of tumors (23)(24)(25)(26)(27). In OSCC, more and more -196 (32).…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs and miRNAs are interrelated with each other to form a lncRNAmediated ceRNA regulatory network. Increasing evidences show that this network of ceRNAs is closely related to tumorigenesis (19). To date, studies have uncovered numerous lncRNA-mediated ceRNA regulatory networks in ESCC (20).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, transwell assays showed that inhibition of miR-206 could reverse the inhibitory effect of sh-Linc1749808 on 97H cell motility. LncRNAs that function as ceRNAs is involved in diverse biological processes in HCC cells, such as tumor cell proliferation, EMT, invasion, metastasis and chemoresistance [28]. The EMT program is linked to metastasis because it causes the increased motility/invasiveness, related to a mesenchymal cell state, and cell separation from the primary tumor mass can be identified as the first step of the invasion-metastasis cascade [29].…”
Section: Discussionmentioning
confidence: 99%